Brief intermittent intense exercise as interoceptive exposure for panic disorder: a randomized controlled clinical trial - Muotri, Ricardo William; Luciano, Alan Campos; Garrudo Guirado, Alia; Lotufo Neto, Francisco; Bernik, Márcio (Frontiers in Psychiatry, 2026)
BackgroundInteroceptive exposure (IE) to feared bodily sensations is a core component of cognitive–behavioral therapy for panic disorder (PD), but standard office-based IE can be perceived as aversive and tedious, potentially limiting engagement. Vigorous physical exercise may provide a more acceptable and health-promoting way to elicit interoceptive cues. Objective: To examine the feasibility and efficacy of a brief intermittent intense exercise (BIE) program, used as an IE strategy, compared with Jacobson’s relaxation training (RT) in treatment-free patients with PD.MethodsIn this prospective, parallel-group, randomized, assessor-blinded clinical trial, 72 sedentary adults with PD (34 men; mean age 33.3 ± 7.7 years), free of pharmacological treatment for ≥12 weeks, were allocated to either a 12-week BIE program (n = 37) or RT (n = 35). BIE consisted of supervised walking interspersed with repeated 30-s high-intensity sprints, while RT followed a standardized progressive muscular relaxation protocol. All participants received identical placebo medication. The primary outcome was Panic Agoraphobia Scale (PAS) score, assessed by a blinded rater at baseline and weeks 6, 12, and 24 (follow-up). Secondary outcomes included frequency and intensity of panic attacks, Hamilton Anxiety Rating Scale (HAM-A), and Hamilton Depression Rating Scale (HAM-D) scores.ResultsBoth groups improved over time, but a significant group × time interaction favored BIE on PAS scores (F = 56.1, p < 0.001, η² = 0.46). At week 12, PAS scores were lower in the BIE group than in RT (14.9 ± 5.3 vs. 23.1 ± 9.4; t = −4.72, p < 0.001), and this difference was maintained at week 24 (14.2 ± 5.5 vs. 24.7 ± 8.5; t = −6.07, p < 0.001). At follow-up, BIE also yielded fewer panic attacks (0.7 ± 0.6 vs. 1.5 ± 1.0; t = 3.79, p = 0.003) and lower HAM-D scores (13.3 ± 4.7 vs. 16.4 ± 5.6; t = −2.55, p = 0.013).ConclusionA 12-week BIE program used as interoceptive exposure was feasible and more effective than relaxation training in reducing panic symptom severity and panic attack frequency, with effects sustained for at least 24 weeks. These findings support the incorporation of structured exercise-based IE into PD treatment programs as a low-cost and engaging option.Clinial trial registrationhttps://www.clinicaltrials.gov, identifier NCT06073691.